Social Functions of the Kamang Mudiak Folklore Text: as Inauguration of Local Cultural Heritage - Hidayati Azkiya; Romi Isnanda; Syofiani Syofiani (Universitas Ahmad Dahlan, 2021)
This research is motivated by the weakening of cultural treasures due to the development of the times and technology and modernization. The culture in the Kamang Mudiak area, one of which is in the form of oral literature, is unknown and known to the younger generation. Whereas knowing culture and preserving it is part of strengthening local culture so that it does not disappear with the development of time. Therefore, this study focuses on the social function of the kamang mudiak folklore: strengthening local cultural heritage. It aims to describe the social function of the oral literary text of the Kanagarian folklore Kamang Mudiak. The research method used is descriptive qualitative method. The data of this research are folklore texts in Kanagarian Kamang Mudiak. Data was collected through recording, recording, observing, and interviewing. Meanwhile, to test the validity of the data, this study used triangulation techniques. The results of the study indicate that there are social functions in the Kamang Mudiak folklore text, namely: (a) developing community integration contained in the story text Ngalau Kalam Tabik, Makam Panjang, Salodang, Tuanku Nan Renceh/ Harimau Nan Salapan, Ngalau Tarang Batu Biaro Bansa. (b) (b) Social Control Tools contained in the story text Salodang, Tuanku Nan Renceh/ Harimau Nan Salapan, Ngalau Tarang Batu Biaro Bansa. (c) Strengthening social solidarity contained in the story